Smart Trash Can Design in Gandaria Elementary School Based on Internet of Things - Fadilah Ramdani; Saludin Muis, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Waste management at SDN Gandaria Utara 08 Pagi is still manual, such as the lid of the trash can that must be opened by itself and the absence of a system to detect full garbage. This causes garbage to often be scattered, causing odors, and disturbing the cleanliness of the school environment. This research aims to create smart trash cans based on the Internet of Things (IoT). This bin uses an ultrasonic sensor to detect fullness, a servo motor to open the lid automatically, and the Blynk app to notify when the bin is full. This system is also equipped with a buzzer as a warning for garbage to be emptied immediately. With the prototype method, this tool is expected to help manage waste more efficiently and maintain the cleanliness of the school environment.